Technical Debt in Computational Science - Hinsen, Konrad (Computing in science & engineering, 2015)
Technical debt is a useful metaphor for understanding the long-term impact of technical choices. The analysis of technical debt has found its place in the software industry, with results that are applicable to scientific software as well. But technical debt is also a useful concept to look at how we use computers in doing scientific research.